Engaging: Creative Placemaking in Macau and Hong Kong - Mendes, Carla de Utra; Simões, José Manuel (Individual, Community & Society: Conflict, Resolution & Synergy, 2014)
Nowadays, contemporary art practices have been expanding into fields outside their own borders. According to Claire Bishop (2012), this expanded field of post-studio practices currently goes under a variety of names: socially engaged art, community-based art, experimental communities, dialogic art, littoral art, interventionist art, participatory art, collaborative art, contextual art and (most recently) social practice. By engaging, artists nurture the sense of belonging and search for an identity of the place they inhabit. In Hong Kong and Macao, as well as in the Pearl River Delta and China in general, the speed of urban transformation is forcing artists to reconsider their participation in the city in order to develop a creative place making process that is according to the new identity of the place. By doing so, they are also included in what has been defined as “creative industries” that tries to build a new image of the urban fabric. Linked with this sort of collective attitude, there is also an attempt to find a sense of local identity that has been disappearing in the face of these major developments. Engaging with the city and the communities may constitute, therefore, a challenge for the young generation, especially in hybrid places such as Hong Kong and Macao, where artists find themselves in an effort to understand the core values of their fragmented identity. In this paper we will analyze some projects that artists are doing in both SAR´s, in order to create a sense of place in this state of transition.